Pengembangan Sistem Informasi Manajemen Ternak Burung Kenari Berbasis Web - Nehru Priyambodo; Nurudin Santoso; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Canary or Serinus Canaria is a very popular bird in Indonesia and was first discovered in Spain. Walnuts have a distinctive feather color and sweet chirp. Many canary breeders do not have specific knowledge about livestock management and only depend on personal experience. Caring for canaries can be a promising business opportunity but many people do not realize the importance of identifying and recording breeding birds so that breeders can see information about bird data clearly and accurately. In addition, all records regarding bird data and financial reports are still done manually so that they are prone to errors or human errors. Based on the description of the problem above, a solution is given, which is to develop an information system to help the management of canaries using web technology, namely MERN (MongoDB, Express, React, and NodeJS). The developed system has the main feature to collect data on canary breeding and all financial activities during the cultivation process. This research uses the waterfall model development method with an object approach. The information system runs on a web platform so that it is tested for usability and compatibility to find out how easy the system is to use and recommendations for a suitable web browser for the system. Usability test results produce 74.5% which can be categorized as "Good". Besides compatibility testing is 100% valid.